Audiovisual programs as authentic language input for second language acquisition in informal settings / Taher Bahrani - Bahrani, Taher (2013)
For second language acquisition (SLA), having access to language input is critical. Although the theories of SLA attach different importance to the role of language input, they all acknowledge the need for it (Ellis, 2008). Learners of English as a second (ESL) or a foreign language (EFL) are always encouraged to avail themselves of all forms of authentic language input within the classroom and beyond. In contexts with limited social interaction in the English language, however, various audiovisual technologies are available to be utilized as sources of authentic language input for enhancing language learning in both formal and informal learning settings. Although the growth of audiovisual applications and their rapid development in transforming the process of learning is unbelievable (Mayya, 2007), the empirical evidence to support the use of audiovisual technologies on the language development of learners is not much. This research was aimed to fill this gap to provide the empirical evidence on the effectiveness of exposure to various audiovisual programs as sources of authentic language input in informal settings on the language proficiency development of learners. Additionally, the study was interested to investigate the effectiveness of this exposure on the language learners of different levels of language proficiency. To this end, a quantitative research design was employed utilizing a pre-post tests design, an adapted survey design and a factorial design. 75 language learners majoring in teaching of English as a second language (TESL) were assigned to three language proficiency levels based on their scores on an IELTS (parallel) pre-test: low (N=25), intermediate (N=25), and upper-intermediate (N=25) levels. The instruments for data collection were a self-report sheet and a set of parallel IELTS (equivalent) pre-post tests. During the 16-week study, all the participants were asked to record the amount and type of exposure of their preferred audiovisual program(s) in a self-report sheet. The data obtained from the self-report sheets indicated that the intermediate and upper-intermediate participants preferred movies and news broadcast more than the other audiovisual programs while the low level participants preferred cartoons. Moreover, the results of the post-test indicated that the intermediate and the upper-intermediate language learners showed significant improvement in their language proficiency, while, this for the low level language proficiency learners who revealed an improvement, was not statistically significant. In relation to the type and amount of exposure to the various audiovisual programs as sources of language input to develop SLA in both EFL and ESL contexts, the findings support the importance of choice of authentic audiovisual input which has a more significant impact on language development compared to the amount of exposure. These findings have pedagogical implications for the selection of audiovisual programs for the different levels of language proficiency for second language learning and acquisition.